P2X7 Receptor Agonist 2′(3′)-O-(4-Benzoylbenzoyl)ATP Differently Modulates Cell Viability and Corticostriatal Synaptic Transmission in Experimental Models of Huntington’s Disease - Martire, Alberto; Pepponi, Rita; Liguori, Francesco; Volonté, Cinzia; Popoli, Patrizia (Frontiers in Pharmacology, 2021)
Huntington’s disease (HD) is a life-threatening neurodegenerative disorder caused by long CAG repeats in the exon 1 of the huntingtin gene that leads to selective loss of medium-sized spiny neurons (MSNs) in the striatum. Altered levels and functions of the purinergic ionotropic P2X7 receptors (P2X7Rs) have been found in animal and cellular models of HD, suggesting their possible role in the pathogenesis of the disease; accordingly, the therapeutic potential of P2X7R antagonists in HD has been proposed. Here we further investigated the effects of P2X7R ligands in vitro and in ex vivo HD experimental models. In ST14A/Q120 rat striatal cells, we found a reduction of P2X7R expression; however, the P2X7R agonist BzATP induced cellular death and this effect was fully reversed by the antagonist OxATP. Moreover, in corticostriatal slices from symptomatic R6/2 mice, BzATP reduced the synaptic transmission to a larger extent than in WT mice. Such an effect was accompanied by a concomitant increase of the Paired-Pulse Ratio, suggesting a presynaptic inhibitory action. This was confirmed to be the case, since while the effects of BzATP were unaffected by the P2X7R antagonist OxATP, they were blocked by the adenosine A1 receptor (A1R) antagonist DPCPX, indicating BzATP hydrolysis to Bz-adenosine and consequent activation of A1Rs as a mechanism. Taken together, these data point out that: 1) P2X7R expression and activity are confirmed to be altered in presence of HD mutation; 2) in some experimental settings, such an abnormal functioning can be ascribed to presynaptic A1Rs activation.